KEPERCAYAAN LOKAL DALAM MANTRA DAYAK BAKUMPAI DI KALIMANTAN SELATAN - Agus Yulianto (ppjbsip, 2022)
Abstract: This study aims to find out the forms of local beliefs contained in the Bakumpai mantra and the correlation of these local beliefs with the lives of the Bakumpai people today. The problem in this study is how are the forms of local beliefs contained in the Dayak Bakumpai mantra and whether there is a correlation between these local beliefs and the current life of the Bakumpai Dayak community. This research uses a qualitative descriptive method with literature study techniques. Based on the results of the analysis, it can be seen that the local beliefs contained in the Bakumpai mantra include: belief in the existence of crocodile stealth; belief in the existence of ancestral spirits that they can still contact; belief in the existence of ethereal beings; belief in the existence of ghosts; and belief in spells that can lure the opposite sex.